Morphologically controlled ZnO nanostructures as electron transport materials in polymer-based organic solar cells. (20th October 2015) - Choi, Kyu-Chae; Lee, Eun-Jin; Baek, Youn-Kyoung; Lim, Dong-Chan; Kang, Yong-Cheol; Kim, Yang-Do; Kim, Ki Hyun; Kim, Jae Pil; Kim, Young-Kuk
Graphical abstract: Highlights: Enhanced efficiency of solar cells using ZnO nanocrystals for charge transport. Morphology of the charge transport layer is controlled. Mixture of nanoparticles and nanorods are advantageous for cell efficiency. ABSTRACT: The morphology of ZnO electron transport layers based on ZnO nanoparticles were modified with incorporation of ZnO nanorods via their co-deposition from mixed colloidal solution of nanoparticles and nanorods. In particular, the short circuit current density and the fill factor of the constructed photovoltaic device were simultaneously improved by applying mixture of ZnO nanoparticles and nanorods. As a result, a large improvement of power conversion efficiency up to 9% for the inverted organic solar cells having a blend of low band gap polymers and fullerene derivative as an active layer was demonstrated with the morphologically controlled ZnO electron transport layer.